Hybrid polycaprolactone/polyethylene oxide scaffolds with tunable fiber surface morphology, improved hydrophilicity and biodegradability for bone tissue engineering applications. Issue 12 (13th August 2018) - Remya, K. R.; Chandran, Sunitha; Mani, Susan; John, Annie; Ramesh, P.
Abstract: In the present study, we attempt to modify Polycaprolactone (PCL) by blending it with a water soluble polymer Polyethyleneoxide (PEO) having two different molecular weights (Mv 1, 00, 000 and 6, 00, 000) using electrospinning technique. The effect of PEO molecular weight and blend ratio on fiber morphology, porosity, surface wettability, static and dynamic mechanical properties of PCL was investigated. In vitro degradation studies in phosphate buffer saline (PBS) at 37 °C demonstrated formation of pores on fiber surface especially in blend scaffolds with 50:50 ratios. In vitro studies using human osteoblast sarcoma (hOS) cell lines on blend scaffolds showed improved cellular response with good cell adhesion, viability and proliferation. The study revealed that incorporation of PEO on PCL scaffolds complemented the properties of PCL and facilitated fabrication of scaffolds with improved hydrophilicity, mechanical property and tunable degradation profile with better cell viability which makes it an ideal candidate for bone tissue engineering applications.